The enzymatic de-epithelialization technique determines denuded amniotic membrane integrity and viability of harvested epithelial cells - Trosan, Peter; Smeringaiova, Ingrida; Brejchova, Kristyna; Bednar, Jan; Benada, Oldrich; Kofronova, Olga; Jirsova, Katerina (PloS one, 2018)
The human amniotic membrane (HAM) is widely used for its wound healing effect in clinical practice, as a feeder for the cell cultivation, or a source of cells to be used in cell therapy. The aim of this study was to find effective and safe enzymatic HAM de-epithelialization method leading to harvesting of both denuded undamaged HAM and viable human amniotic epithelial cells (hAECs). The efficiency of de-epithelialization using TrypLE Express, trypsin/ ethylenediaminetetraacetic (EDTA), and thermolysin was monitored by hematoxylin and eosin staining and by the measurement of DNA concentration. The cell viability was determined by trypan blue staining. Scanning electron microscopy and immunodetection of collagen type IV and laminin α5 chain were used to check the basement membrane integrity. De-epithelialized hAECs were cultured and their stemness properties and proliferation potential was assessed after each passage. The HAM was successfully de-epithelialized using all three types of reagents, but morphological changes in basement membrane and stroma were observed after the thermolysin application. About 60% of cells remained viable using trypsin/EDTA, approximately 6% using TrypLE Express, and all cells were lethally damaged after thermolysin application. The hAECs isolated using trypsin/EDTA were successfully cultured up to the 5th passage with increasing proliferation potential and decreased stem cell markers expression (NANOG, SOX2) in prolonged cell culture. Trypsin/EDTA technique was the most efficient for obtaining both undamaged denuded HAM and viable hAECs for consequent culture.
Keywords: laminin; kultivované buňky; epitelové buňky; Microscopy, Electron, Scanning; SOXB1 Transcription Factors; Amnion; DNA; Collagen Type IV; mikroskopie elektronová rastrovací; Epithelial Cells; Cell Proliferation; Nanog Homeobox Protein; Edetic Acid; nanog; trypsin; Re-Epithelialization; Cells, Cultured; EDTA; Trypsin; Humans; Laminin; amnion; kolagen typu IV; transkripční faktory SOXB1; reepitalizace; Cell Survival; viabilita buněk; proliferace buněk; lidé